Awareness of UiTM staff about National Integrity Plan (NIP)/ Abang Zulazan Shah Abang Zaidi ... [et al.] - Abang Zaid, Abang Zulazan Shah; Abdul Rahim, Azizul Helmi; Abang Julaihi, Dayang Nur Izzati Asrida; Mohd Roselee, Faridah; Ngah Said, Mohd Fahmi (2010)
The National Integrity Plan is an integrity plan that evolved from the aspirations Of our people and our country. It has been formulated in accordance with our own mould with Malaysians of all ethnic and religious groups as its stakeholders. The plan takes into account the views and suggestions presented at a series of national seminars, involving representatives from almost all sectors of the society. Thus the National Integrity Plan (NIP) reflects the hopes and aspiration of both the leadership and the people.